Visual dependence affects postural sway responses to continuous visual field motion in individuals with cerebral palsy. (17th November 2018) - Yu, Yawen; Lauer, Richard T.; Tucker, Carole A.; Thompson, Elizabeth D.; Keshner, Emily A.
ABSTRACT: The current study aimed to explore the impact of visual dependence on sensorimotor coupling of postural sway and visual motion in adults and teens with spastic cerebral palsy (CP). We hypothesized that individuals with CP would exhibit greater magnitudes of sway than healthy individuals, and the presence of visual dependence (VD) would produce instability in the direction of visual motion. Participants stood in a virtual environment in which the visual scene remained static or continuously rotated 30 degree/second in pitch-up or pitch-down. Increased center of pressure and center of mass responses were observed in the direction of visual scene motion in those with CP. Those with VD exhibited reduced frequency responses in anterior-posterior direction than those who were visually independent. VD suggests deficient sensorimotor integration that could contribute to postural instability and reduced motor function. Individuals with CP who are visually dependent may benefit from more sensory focused rehabilitation strategies. Abbreviations : AP, anterior-posterior; CP, cerebral palsy; COM, center of mass; COP, center of pressure; MDF, median frequency; ML, mediolateral; PD, pitch down (nose down) rotation; PU, pitch up (nose up) rotation; RFT, rod and frame test; RMS, root mean square; SLP, slope of the fitted line; TD, typical development; VD, visual dependence; VI, visual independence; VOR, vestibulo-ocular reflex; VPI, visual perceptual impairment